The Barbarian Principle : Merleau-Ponty, Schelling, and the Question of Nature - Wirth, Jason M., 1963- (Book collections on Project MUSE., 2013)
"Essays explore a rich intersection between phenomenology and idealism with contemporary relevance"--Provided by publisher